Problems and prospects of development in AIC - Zinoviev, A. Y.; Odnoromanenko, Maryna; Однороманенко, Марина Володимирівна; Однороманенко, Марина Владимировна (ТДАТУ, 2019)
Ukraine on the world stage is defined as a potential leader in the production of such foods: grains, sugars, oils, meat, processed milk, vegetables and berries. A great number of companies from different countries of the world want to cooperate, so we are sure that Ukraine will take the first places in the international arena in the near future.
Keywords: agro-industrial complex; economic environment; priority of the agrarian sector; ventures